Child attachment security in gay father surrogacy families: Parents as safe havens and secure bases during middle childhood. Issue 3 (3rd May 2020) - Carone, Nicola; Baiocco, Roberto; Lingiardi, Vittorio; Kerns, Kathryn
ABSTRACT: Child attachment security and utilization of parents as safe havens and secure bases were compared in 33 surrogacy children with gay fathers and 37 donor-conceived children with lesbian mothers during middle childhood. Assessments included data coded from parent–child interactions, interviews, and questionnaires administered to children and both parents. Findings indicated that children of gay fathers perceived high attachment security and their scores did not differ from those of children with lesbian mothers or from normative scores of children with heterosexual parents. Children's greater attachment security was associated with higher levels of parental warmth, responsiveness, and willingness to serve as an attachment figure; lower levels of parental negative control and rejection; and the child's younger age. Finally, children used the primary attachment figure more as a safe haven and the secondary attachment more as a secure base, though they reported high levels of both types of support from both parents.